2013
DOI: 10.1093/alcalc/ags133
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the ‘What Do You Drink’ Web-based Brief Alcohol Intervention in Reducing Heavy Drinking among Students: A Two-arm Parallel Group Randomized Controlled Trial

Abstract: The WDYD intervention was not effective in reducing the alcohol measures among heavy drinking students at 1- and 6-month post-intervention. However, there is preliminary evidence that the WDYD intervention is effective in lowering drinking levels for subgroups of heavy drinking students in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 50 publications
1
31
0
10
Order By: Relevance
“…Interventions resulting in significant effects included general personalised normative feedback (two studies), gender-specific feedback (one study), interactive online education consisting of tailored feedback, goal setting, stress management, and harm reduction (one study), and an online BI combining personalised normative feedback, goal setting, action planning, and enhancement of refusal self-efficacy (one study). The latter comprised an online screening test, together with personalised normative feedback and advice for drinking in accordance with lowrisk drinking guidelines, a personal drinking profile, estimates of calorie intake from alcohol, drinking-related expenditure, and normative comparisons of drinking levels (Voogt, Kuntsche, Kleinjan, Poelen, & Engels, 2014;Voogt, Poelen, Kleinjan, Lemmers, & Engels, 2013). Further, the intervention instructed students to set drinking goals and provided tips on how to resist drinking in different situations with a view to enhancing their refusal self-efficacy.…”
Section: Individual Interventions (Iv): Digital Interventionsmentioning
confidence: 99%
“…Interventions resulting in significant effects included general personalised normative feedback (two studies), gender-specific feedback (one study), interactive online education consisting of tailored feedback, goal setting, stress management, and harm reduction (one study), and an online BI combining personalised normative feedback, goal setting, action planning, and enhancement of refusal self-efficacy (one study). The latter comprised an online screening test, together with personalised normative feedback and advice for drinking in accordance with lowrisk drinking guidelines, a personal drinking profile, estimates of calorie intake from alcohol, drinking-related expenditure, and normative comparisons of drinking levels (Voogt, Kuntsche, Kleinjan, Poelen, & Engels, 2014;Voogt, Poelen, Kleinjan, Lemmers, & Engels, 2013). Further, the intervention instructed students to set drinking goals and provided tips on how to resist drinking in different situations with a view to enhancing their refusal self-efficacy.…”
Section: Individual Interventions (Iv): Digital Interventionsmentioning
confidence: 99%
“…In 5 trials rated as low to moderate risk of bias in students (37,48,49,52), e-interventions resulted in no statistically significant reduction in binge drinking (MD, −0.1 episodes [CI, −0.6 to 0.4]) at 6-month follow-up. Effect sizes had moderate heterogeneity (Q = 8.8; P = 0.066; I 2 = 55%); 1 trial rated as low risk of bias that studied human support reported significant effects (44).…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…Although some of these studies demonstrated a number of strengths, achieving a diverse selection of student population and drinking cultures (Kypri et al, 2014), utilising a randomised controlled design (Hester et al, 2012), and achieving high retention rates (Palfai, Zisserson & Saitz, 2011), some had issues of being underpowered (Cunningham et al, 2012), and potential social desirability bias (Hester et al, 2012) Improving knowledge, self-efficacy and awareness of social norms was found to significantly reduce weekly alcohol consumption (Voogt et al, 2014b), and was particularly effective in lowering drinking levels for subgroups of heavy drinking students in the short-term (Voogt et al, 2013b). It was also found that those in the experimental condition experienced higher social pressure Drinking Refusal Self-Efficacy (DRSE) compared to participants in the control condition, which was sustained after 6 months (Voogt et al, 2014a).…”
Section: Web-based Interventionsmentioning
confidence: 99%
“…It was also found that those in the experimental condition experienced higher social pressure Drinking Refusal Self-Efficacy (DRSE) compared to participants in the control condition, which was sustained after 6 months (Voogt et al, 2014a). Voogt et al, (2013b;2014a;2014b) employed a rigorous methodology throughout each of the 3 papers. A high retention rate of the large sample size (N = 907) ensured stable findings and the ability to detect significant differences, however, the generalisability of the study is reduced by the university specific population and convenience sampling strategy.…”
Section: Web-based Interventionsmentioning
confidence: 99%